Students’ motivation to fitness classes at technical university - Balitskaya, E.P. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The aim of the study is to determine the motives of students to fitness classes at technical university. The results of the survey of students I - II courses motivation for fitness classes in physical education. The survey involved 182 students (173 girls and 9 boys) of technical faculties. Found that most of the students have been studying fitness for entry the university. The main motivation for fitness training is to increase the level of physical fitness and self-confidence, as well as the development of special vocational important physical qualities, which in the future will contribute to the professional activities of the students. It is shown that universities are engaged in fitness in 13.82% of the students. Swimming is the clear leader - 18.37% and athletic gymnastics - 17.19%. Also popular are sports games - 26.77% (football, basketball, volleyball, tennis). Also are visited sections in gymnastics, wrestling, boxing, and tourism.